Letter (copy) - Hunt, Charles
1936-11-16 041-0012-004 - 2 - Clarke when he was here discussed the question of transport with Poole, and asked for any suggestions as to how the proper vehicles could be obtained, and it was suggested to him by this comrade that they should be bought in Paris or Marseilles and equipped with a body similar to the ambulances which are being used exclusively by the Spanish Government. Apparently, this advice if given to the Committee, was also ignored. With reference to the new vehicles, the stretcher units are mounted on the floor of the body of the vehicle which is five foot from the ground and this makes it almost a physical impossibility to lift a seriously wounded patient into the top runway, and at least means considerable discomfort being caused to the patient. Secondly, they are sprung for a two-ton load and as they are never called upon to carry this weight the springs remain ineffective. This Hospital has the reputation of being the most efficient on the Aragon Front except as to its transport, and it should be apparent at least to those of you who are in the medical profession that much of the good work performed by our surgeons and doctors is undone by the transport facilities. In addition there is also the difficulty of obtaining spare parts for Renaults in Spain. In conclusion may we add that it would appear to us that we were sent out here as a gesture, and any gesture ceases to be of use if the keynote of any help given is not quality and efficiency. We are efficient and there is no question as to the quality of the work that is being done here, but we must have really efficient ambulances in order that this work may be effective and save pain, and even the loss of life. We have discussed this question some length and have come to the conclusion that the only person really qualified to report on this question is one of our own members who is aware of our requirements and also of the conditions they have to withstand. We do earnestly suggest therefore, that a reliable member of the section returns to England in order to meet you and discuss with you the urgent need for you to purchase at least two new ambulances for service here. He will receive instructions from us as to our requirements here and we trust that this advice and suggestions will not be ignored but that you will bear in mind the fact that he has seen some considerable service here and is fully qualified to insist on our advice being followed. Yours fraternally, (Received unsigned, prepared by Charles Hunt.) The substance of this report is, in my opinion, correct though it represents a considerable watering down of some of HUNTS verbal statements. K.W.C.S.L. 16.11.36. 292/946/41/12(iv)